Flexible and low-cost binderless capacitors based on p- and n-containing fibrous activated carbons from denim cloth wastes - Rosas-Martínez, Juana María; Cordero-Alcántara, Tomás; García-Mateos, Francisco José; Rodríguez-Mirasol, José (My University, 2018)
Activated carbon cloths have been prepared from denim cloth wastes (DCWs) through chemical activation with H3PO4. The effect of the H3PO4/DCWs impregnation ratio and the carbonization temperature on the porous texture, the chemical composition, the fibers morphology, and the electrochemical performance has been studied. Low H3PO4/DCWs impregnation ratios lead to flexible and microporous activated carbons cloths, whereas more fragile and rigid activated carbon cloths with higher external surface area are produced upon increasing the amount of H3PO4. The increase in the carbonization temperature allows for obtaining a more ordered and conductive carbon structure. The activated carbon prepared at 900 ºC with a H3PO4/DCWs impregnation ratio of 0.5 (w/w) exhibits the best performance as electric double layer capacitor. This electrode shows a specific surface area of 2016 m2 g-1 and the highest registered gravimetric capacitance (227 F g-1). Moreover, its flexibility minimizes the ohmic resistance of the electrode, thus increasing the feasibility of working at higher current densities than the other synthesized electrodes.
Keywords: Carbón activado; Porous carbon; Electrodes; Activated carbon cloth; Chemical activation